Роздрібна торгівля в сільській місцевості УРСР у післявоєнний період (1945– 1991 рр.) - Сидорович, О. (Сiверянський лiтопис, 2015)
Cтаття покликана актуалізувати проблему функціонування роздрібної торгівлі
в сільській місцевості УРСР у післявоєнний період. Здійснена спроба проаналізувати
роль споживчої кооперації України у цій галузі, виокремити причини перманентного
товарного дефіциту в повоєнному українському селі. Статья призвана актуализировать проблему функционирования розничной торговли в сельской местности УССР в послевоенный период. Осуществлена попытка проанализировать роль потребительской кооперации Украины в этой области, выделить
причины перманентного товарного дефицита в послевоенном украинском селе. One of the key elements of social protection is to provide consumer goods. Of particular
importance, this problem is in rural areas, where the provision of essential commodities is at a
lower level than in the city. The reasons for this phenomenon are complex. The dramatic changes
which took place in the country in the early 1990’s were connected with the transition from
a command economy to a market economy. The transformations associated with the collapse
of the Soviet Union hit the agricultural sector the hardest. Dismantling of collective and state
farm system in the absence of targeted strategies for rural development in the post-Soviet
period caused a chain reaction of destruction of labor relations, cultural and educational fields
and retailers in the country. However, one of the main reasons in our opinion is a historic
tradition which was supported by the government in the days of the Soviet Union and which
lay in provision of a residual village with the remaining principle. Retail sales in rural areas
in the Soviet times was conducted through the system of consumer cooperatives, which during
the post-Soviet transformation for various reasons suffered considerable losses.
The article brings up the problem of functioning of retail in rural areas of the USSR in the
postwar period. An attempt is made to analyze the role of consumer cooperation of Ukraine in
this sphere, to isolate the causes of permanent trade deficit in the postwar Ukrainian village.